Mineral composition and availability, dietary fiber content and fermentability characteristics of Caulerpa lentillifera and Kappaphycus alvarezii - Alcantara, James David S. (Animo Repository, 2016)
Seaweeds like Caulerpa lentillifera and Kappaphycus alvarezii are used as main ingredient in Filipino delicacies popular here and abroad. They have been branded as healthy food being rich in dietary fiber, minerals, vitamins, proteins, phytochemicals, with low lipid content. With that being said, the mineral availability, dietary fiber and short chain fatty acid content of Caulerpa lentillifera and Kappaphycus alvarezii were investigated. The proximate composition and mineral analysis were investigated using AOAC methods and computation by difference was done for the computation of total carbohydrates. While the method of Trinidad et al was used for the mineral availability analysis and the method of Mcburney and Thompson for in vitro fermentation. In this study, Caulerpa lentillifera has higher total iron, zinc and calcium (430.931.46, 1.090.19 and 988.445.07 mg/100g, respectively) compared with Kappaphycus alvarezii (11.340.14, 0.290.01 and 262.982.83 mg/100g, respectively). Caulerpa lentillifera and Kappaphycus alvarezii have high calcium availability (94.102.53 %Ca and 96.452.32 %Ca, respectively) compared with its iron and zinc availability. Both samples also exhibited high amounts of dietary fiber. The soluble, insoluble and total dietary fiber content of Kappaphycus alvarezii (16.730.03, 42.241.04 and 58.971.01 g/100g, respectively) was higher than that of Caulerpa lentillifera (3.500.41 g/100g for soluble, 27.170.09 g/100g for insoluble, 30.670.32 g/100g for total dietary fiber). Kappaphycus alvarezii produced both propionate (35.53 2.00 g/100g) and butyrate (3.19 0.16 g/100g) while Caulerpa lentillifera only produced propionate (15.92 0.45 g/100g). This may indicate that both seaweed samples may have a protective effect in the prevention of chronic diseases.